Relationship marketing, long term orientation and customer loyalty in higher education - Abubakar, Muhammad Mujtaba; Mohd Mokhtar, Sany Sanuri (MCSER Publishing, Rome-Italy, 2015)
Recent policy changes, globalization and competition have called for the application of marketing models in the management of the higher educational institutions around the world. This study conceptualizes and empirically validates a model exploring the relationship between key relational constructs and customer loyalty among university students.A sample of 416 Nigerian university students was taken through multi-stage cluster sampling procedure.Partial Least Squares structural equation modelling was employed to analyse the data.Results suggest that the constructs of bonding, communication and personalization have significant effect on student satisfaction and trust which in turn predict student loyalty.Further, individual student long term orientation has moderating effect on the path between satisfaction and loyalty as against the path between trust and loyalty Theoretical and practical implications of the study were discussed and a conclusion drawn.